Effect of type of nitrogen sources and concentration on protease production: fish waste hydrolysate as a potential low cost source - F. H., Zainuddin; Chua, Gek Kee; Chew, Few Ne; Rozaimi, Abu Samah; Siti Hatijah, Mortan; Noraziah, Abu Yazid (IOP Publishing, 2020)
Fish waste hydrolysate is obtained from hydrolysis process of a fishery industry waste. It can be a good substrate source for the production of protease via a fermentation process. Protease covers above than 50% of the global industrial enzymes market and is regarded as an enzyme which is widely used in many applications. This research aims to determine the effect of the type of nitrogen sources and nitrogen source concentration on protease production from the fish waste hydrolysate. The experiments were done using one factor at a time (OFAT) of type of nitrogen sources and nitrogen source concentration in submerged fermentation (SmF) of 10% (v/v) Bacillus cereus (ATCC 10876). In the first stage, the variation of type of 1% (w/v) nitrogen sources such as fish waste hydrolysate, beef extracts, yeast extracts, tryptone, peptone and skim milk powder that mixed with the basal media were compared to evaluate the highest protease production. Then, the concentration of fish waste hydrolysate was varied from 1% to 3% (w/v) to analyse the production trend of protease. The protease activity and total protein content were then analysed by protease assay using tyrosine as a standard and Bradford method, respectively. Upon the observation, 1% (w/v) nitrogen sources on protease production revealed that the fish waste hydrolysates and beef extracts were capable to produce a high amount of protease (23.659 ± 0.38 U/mL and 28.7631 ± 0.59 U/mL, respectively). Among the concentration tested, 3% (w/v) of fish waste hydrolysate was found to be the highest protease production (190.85 ± 0.38 U/mL). Therefore, the fish waste hydrolysate has a potential as a low-cost source for protease production.